Strategi Komunikasi Pemasaran Alfamart Dalam Meningkatkan Penjualan Melalui Aplikasi Alfagift - Dhira Vanesca Syahputri Efendi; Muhammad Hilmy Aziz; Ratna Setyarahajoe (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2024)
This research examines the implementation of Alfamart's marketing communication strategy in increasing sales through the Alfagift application. This research aims to analyze the marketing communication strategy carried out by Alfamart through the Alfagift application. This research uses descriptive qualitative research methods and makes observations on the Alfagift application and the services provided by Alfamart staff to increase sales. The results of this research show that Alfamart's marketing communication strategy in increasing sales through the Alfagift application is running optimally, there are 2 strategies in an effort to increase sales, namely an attractive strategy and a pushing strategy carried out by Alfamart. Apart from that, there are attractions that the Alfagift application has, such as discount promos that can only be enjoyed if you shop on the Alfagift application, ease of shopping with ready-to-deliver services, as well as a feature with a point number that customers can have every time they shop on the Alfagift application. Later it can be exchanged for a discount on your next purchase. The significant increase in Alfamart Semambung sales in 2020 will be a benchmark for the success of marketing communication strategies in increasing sales by 30% through the Alfagift application.